(3GdeYLe Gdeaff HGdeYLe GdeYfhfs - (3YHO GdHGSW Hf Ndjd Hf TGgjf GdedWi GdbGgQi GdMfajs; (3YHO GdHGSW GdedWj , YHO GdHGSW Hf Ndjd Hf TGgjf GdedWj GdbGgQj, Rjf GdOjf,J (B920 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd NHQ GdCNjGQ NjQ GdCNHGQ s
(3BNQgG (B:s
(3BNQ eG ajg ef GdJQGLe GSe (B" (3LGfHc (B" s
(3hgh cJGH ai GdJQGLes
(3LQOg GdeDda ef cJGHg GdeSei (B: (3GdQhV GdHGSe ai MhGOK GdYeQ hGdJQGLes
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B68s
Keywords: (3GdJGQjNs